Maintaining Legal Certainty in Indonesia: The Role of Legal Instruments in Protecting Auction Buyer - Rini, Tifani; Paserangi, Hasbir; Deviany, Oky; Maskun, Maskun; Ratnawati, Ratnawati (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2024)
The implementation of a mortgage auction carries a high potential for lawsuits to cancel the auction due to objections from the debtor. This study analyzes the rights of heirs over assets encumbered with a mortgage based on credit agreements, aiming to provide legal certainty for auction winners and protection for mortgage auction winners. The research is normative with a legislative and conceptual approach. The findings show that inherited property mortgaged by the deceased, the heirs must fulfill the obligations. If they refuse, the bank can auction the property. However, auction winners often face legal disputes from heirs. For example, in Case No. 453/Pdt.G/2021/PN Mks, heirs sued Bank BRI and the auction winner, claiming ownership of the mortgaged property, despite the auction winner having valid proof. A similar issue occurred in Case No. 240/ Pdt.G/2019/PN Mks, where heirs sued PT Penanaman Modal Madani and the auction winner over a mortgaged asset due to non-performing loans. In both cases, auction winners encountered conflicts and difficulties in executing their rights despite winning the auction legally. This highlights that auction winners often lack adequate legal protection, especially in disputes with heirs. Despite existing auction regulations, legal uncertainty remains, and protection for auction winners needs improvement.